Protection of Children in Conflict with the Law in the Prosecution Process by the Public Prosecutor - Rizky Chairunisya Ramadhani; Tarmizi Tarmizi; Tengku Erwinsyahbana (Lembaga Riset Mutiara Akbar, 2025)
The handling of children in conflict with the law requires a special approach prioritizing their best interests and future. This study analyzes the legal protection provided to children during the prosecution process by the Public Prosecutor at the Belawan District Attorney’s Office and identifies obstacles in implementation. Using an empirical juridical method with a qualitative approach through field interviews and document analysis, the study reveals that the protection of children’s rights has not been fully implemented according to the restorative justice principles mandated by Law No. 11 of 2012 on the Juvenile Criminal Justice System. Challenges include the limited number of trained child prosecutors and the inconsistent application of the ultimum remedium principle. The findings highlight the gap between normative legal frameworks and practical realities, emphasizing the need to strengthen prosecutor capacity and adopt holistic approaches combining legal, psychological, and social dimensions.